Optimization design of nickel-titanium shape memory alloy anti-loose gaskets based on ABAQUS numerical simulation - Tianxiang Xue; Xinmei Li; Shuai Suo; Wen Li; Yanjiang Bu; Dongting Wu (Materials Research Express)
This paper addressed the issue of maintaining long-term stability under complex conditions with traditional anti-loose gaskets used in the power industry. It proposed a design for an anti-loose gasket, exploiting the super-elasticity, shape memory effect, and high damping characteristics of nickel-titanium shape memory alloys (NiTi-SMA). The deformation and stress during its ‘pre-tightening-tightening-unloading’ process were simulated using ABAQUS software, and the impact of geometric structural parameters on its performance was analyzed. Findings reveal that the maximum deformation and stress were focused at the junction of the gasket and the bolt during loading. Conversely, the residual stress and deformation predominantly resided on the gasket’s shoulder and were relatively minimal post-unloading, confirming its super-elasticity. After optimization, it was concluded that the convex thickness of the gasket’s bending section should be 2 mm–3 mm, the transverse distance 4 mm–7 mm, the difference in the inner and outer radii of the upper contact surface ring 2 mm–4 mm, and the difference in the inner and outer radii of the lower contact surface ring should be greater than or equal to 2 mm. This study provides theoretical support and design reference for implementing this alloy in the field of anti-loose, thus contributing to the development of high-performance anti-loose components.